PENGEMBANGAN E-LKPD IPA MATERI EKOSISTEM BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS V SEKOLAH DASAR - Haryanti, Minche; Widi Winarni, Endang; Muktadir, Abdul; Agusdianita, Neza; Juarsa, Osa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the characteristics, determine the validity, examine the practicality, and analyze the effectiveness of a Problem-Based Learning (PBL)-based electronic student worksheet (E-LKPD) on ecosystem topics in improving the cognitive learning outcomes of fifth-grade elementary school students. This study employed a Research and Development (R&D) approach using the ADDIE model, covering the analysis, design, development, implementation, and evaluation stages. The research subjects comprised expert validators for material, language, and graphic design, a fifth-grade teacher, and 21 fifth-grade students of SD Negeri 42 Kota Bengkulu. Data were collected through interviews, needs-analysis questionnaires, expert validation sheets, learning-implementation observation sheets, teacher and student response questionnaires, and a cognitive learning achievement test administered as a pretest and posttest, then analyzed using Aiken's V, Inter-rater Reliability (IR), response percentage, and the N-Gain test. The results showed that the developed E-LKPD integrates the syntax of Problem-Based Learning into digital learning through Liveworksheet, comprising problem orientation, organizing students, individual and group investigation, presenting findings, and analyzing and evaluating the problem-solving process, aligned with the Learning Outcomes of Phase C in the Merdeka Curriculum. Expert validation on material, language, and graphic design obtained Aiken's V values ranging from 0.67 to 1.00, categorized as moderate to highly valid, with an inter-rater reliability of 100% (near-perfect agreement) on all three aspects. Teacher and student responses reached 90% each, categorized as very good, with 100% implementation of the PBL syntax. The effectiveness test showed a significant improvement in students' cognitive learning outcomes, with the average score increasing from 18.92% in the pretest to 78.17% in the posttest, and an N-Gain score of 0.747, categorized as high. Therefore, the PBL-based E-LKPD is valid, practical, and effective for use in teaching ecosystem topics to fifth-grade elementary school students.